Premenstrual Dysphoric Disorder: A Cross-Sectional Study on Prevalence, Awareness, and Haematological Correlates Among Medical Students - Muhammad Tariq Hamayun Khan, Naeem Amjad, Uzma Asif, Mian Mukhtar Ul Haq, Maryam Shoaib, Amna Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Premenstrual Dysphoric Disorder (PMDD) is a severe mood disorder associated with significant emotional and physical distress during the luteal phase of the menstrual cycle. Despite its clinical relevance, it remains underdiagnosed, particularly among female medical students exposed to high academic stress. Objective: To assess the prevalence, awareness, and haematological correlates of PMDD among female undergraduate medical students in Pakistan. Methods: A cross-sectional study was conducted from June 2022 to June 2023 across three medical colleges: Shahida Islam Medical College, Lodhran; Islam Medical College, Sialkot; and Al-Aleem Medical College, Lahore. A total of 100 female students aged 18–26 years were evaluated using DSM-5-based PMDD diagnostic questionnaires and a structured awareness survey. Haematological parameters including hemoglobin, MCV, WBC count, platelet count, and ESR were analyzed. Data were interpreted using SPSS v26, with p<0.05 considered significant. Results: PMDD was diagnosed in 27% of participants. Only 38% had adequate awareness of the disorder, and just 25.9% of those diagnosed with PMDD recognized the condition. Irregular sleep patterns (p<0.001) and a positive family history of mood disorders (p=0.002) were significantly associated with PMDD. Hemoglobin levels were significantly lower (11.3 ± 0.9 g/dL vs. 12.6 ± 0.8 g/dL, p<0.001), and ESR values significantly higher (25.2 ± 4.8 mm/hr vs. 16.5 ± 4.2 mm/hr, p<0.001) in the PMDD group. Conclusion: PMDD is a common but under-recognized condition among female medical students. Significant associations with anemia, inflammation, and psychosocial stressors highlight the need for increased awareness, mental health screening, and preventive care within academic institutions. Keywords: PMDD, Premenstrual Dysphoric Disorder, medical students, prevalence, awareness, hemoglobin, ESR, DSM-5, Pakistan